Grey Wolf optimization based power management strategy for battery storage of dfig-wecs in standalone operating mode - Nasir Uddin M.; Khairul Amin I.; Rezaei N.; Marsadek M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Battery management systems; Battery storage; Electric batteries; Electric fault currents; Electric load flow; Electric power generation; Energy conversion; Energy management systems; Heuristic algorithms; Optimization; Wind; Wind power; Battery power managements; Bidirectional converter (BDC); Doubly fed induction generator (DFIG); Doubly Fed Induction generators (DFIG); Stand-alone modes; Wind energy conversion system; Wind energy systems; Wind power generation systems; Asynchronous generators